2003
DOI: 10.1080/0003684032000079152
|View full text |Cite
|
Sign up to set email alerts
|

Do informal risk sharing networks crowd out public voluntary health insurance? Evidence from Vietnam

Abstract: Many governments in low-income countries have promoted voluntary health insurance schemes in recent years, with the principal aim of improving access to services amongst those working in the informal economy. Few attempts to understand demand for such schemes exist, particularly in light of the importance of informal social security arrangements for many households. A model of demand for health insurance is developed reflecting this context, and estimated using data from Vietnam. The results show that informal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 21 publications
3
46
3
Order By: Relevance
“…It was hypothesised that people who had not borrowed money or borrowed money from immediate family, relatives or friends only were less likely to enrol in CBHI due to the "negative" effects of bonding social capital. This is supported by a study on voluntary health insurance in Vietnam (Jowett, 2003) which showed that borrowing money from informal financial networks (family and friends)…”
Section: Variablesmentioning
confidence: 61%
“…It was hypothesised that people who had not borrowed money or borrowed money from immediate family, relatives or friends only were less likely to enrol in CBHI due to the "negative" effects of bonding social capital. This is supported by a study on voluntary health insurance in Vietnam (Jowett, 2003) which showed that borrowing money from informal financial networks (family and friends)…”
Section: Variablesmentioning
confidence: 61%
“…However, there is a second argument in the CBHI literature that turns this hypothesis on its head and holds that strong intra-group bonds actually prevent the emergence of successful CBHI (Meessen, 2002, Atim, 1999, Jowett, 2003. An example of this comes from Ghana where, in the face of conflicting loyalties between a CBHI scheme and members of their community, field assistants apparently connived with community members in the practice of evading the stipulation of family membership, a mechanism designed to prevent adverse selection (Atim, 1999).…”
Section: Negative Role Of Bonding Social Capitalmentioning
confidence: 99%
“…Also supporting the negative view of social capital, Jowett (Jowett, 2003), using data from voluntary health insurance (which operates much like CBHI) in Vietnamese provinces, takes issue with Hsiao's (Hsiao, 2001) argument that social capital facilitates collective action and willingness to pay. The results of Jowett's study, which controls for a range of health and socio-economic variables, showed that high levels of two proxies of social capital -perceptions of social cohesion and informal financial networks -were correlated with lower, not higher, rates of take-up of community-based voluntary health insurance, suggesting that intra-community bonding social capital 'crowds out' voluntary health insurance.…”
Section: Negative Role Of Bonding Social Capitalmentioning
confidence: 99%
See 2 more Smart Citations